A ADESÃO PENTECOSTAL DE BANDIDOS E EX-BANDIDOS – UM ESTUDO SOBRE RELIGIÃO E PERIFERIA NA FAVELA DO JARDIM SÃO JORGE EM CIDADE ADEMAR - SP - SILVA, LUCAS BRAGA MEDRADO DA (2015)
The dissertation was concerned to analyze the relationship of thugs and former bandits with Pentecostalism in Fortified Assembly of God in Christ (ADFEC), located at São Jorge Garden slum outskirts of Ademar City, southern region of the capital of São Paulo. Interested in understanding the interactions of these agents and which way the church played its work in a Pentecostal space. The research had as main objective, to examine the approaches of crime and Pentecostalism indicating their breaks and special characteristics. Fieldwork was dedicated in collecting data proving performance of ADFEC together to crime agents, and to what extent the religious affiliation of the agents gained importance. Finally, we reflect on the accession of thugs and former bandits to Pentecostalism and the influence of membership in the community's daily life.